Biomarkers for treatment change and radiographic progression in patients with rheumatoid arthritis in remission: a 5 year follow-up study. (12th July 2020) - Ramírez, Julio; Cuervo, Andrea; Celis, Raquel; Ruiz-Esquide, Virginia; Castellanos-Moreira, Raul; Narváez, José Antonio; Gómez-Puerta, José A; Pablos, José L; Sanmartí, Raimon; Cañete, Juan D
Abstract: Objective: To identify biomarkers of treatment change and radiographic progression in patients with RA under remission. Patients and methods: RA patients in remission (DAS28-ESR <2.6) were selected and followed up for 5 years. An MRI of the dominant hand and an US assessment of knees/hands and serum levels of inflammation/angiogenesis biomarkers were performed at baseline and at 12th month. Synovial biopsies were obtained in patients with Power Doppler signal. Conventional radiographies of hands/feet were taken at baseline and after 5 years. Radiographic progression was defined as the change in the modified Sharp van der Heijde Score at 5 years >10.47 (small detectable change). Results: Sixty patients were included, 81.6% were ACPA+ and 45% were taking biological DMARDs. At baseline, 66.6% had Power Doppler signal. After 5 years, 73.3% of patients remained in remission. Change of therapy was performed in 20 patients (33.3%) and was associated with BMI [odds ratio (OR) 1.3, 95% CI: 1, 1.7], lack of biological DMARD therapy (OR 24.7, 95% CI: 2.3, 257.2), first-year progression of MRI erosions (OR 1.2, 95% CI: 1, 1.3) and calprotectin serum levels (OR 2.8, 95% CI: 1, 8.2). Radiographic progression occurred in six (10%) patients. These patients had higher first-year progression of MRI erosions ( P = 0.03) and bone oedema ( P = 0.04). Among 23 patients undergoing synovial biopsy, mast cell density was independently associated with clinical flares. Conclusions: One-third of RA patients lost clinical remission and changed therapy throughout the 5 years of follow-up, which was independently associated with BMI, lack of biological DMARDs therapy and first-year progression of MRI erosion score and calprotectin serum levels. Significant radiographic progression was uncommon.